Highly sensitive detection of lead ions and cadmium ions based on ZIF-8-NH2 enhanced by carbon nanotubes and bismuth film. Issue 2 (April 2023) - Chen, Xingguang; Xie, Tingting; Lu, Chaoqun; Chu, Jiyang; Li, Wenzhe; Lin, Rui; Wu, Dianhui; Gu, Qianhui
Abstract: Heavy metal ions are common pollutants in the water environment, which have caused severe damage to the water environment, so it is necessary to monitor them. In this work, an electrochemical sensor based on aminated Zn (Ⅱ) metal-organic framework (ZIF-8-NH2 ) enhanced by carbon nanotubes (CNTs) and bismuth (Bi) film was prepared for simultaneous detection of lead ions (Pb 2+ ) and cadmium ions (Cd 2+ ) in water samples. The ZIF-8-NH2 /CNTs was prepared by electrostatic assembly with ultrasonic assistance. The results show that the combination of ZIF-8-NH2 and CNTs not only can promote the three-dimensional distribution of CNTs, but also compensated for the poor electrical conductivity of ZIF-8-NH2 . Furthermore, the deposition of Bi film in situ promoted the enrichment of Pb 2+ and Cd 2+ in the detection process, further enhancing the electrochemical signal. Based on this, the prepared sensor displayed good linear ranges of 0.050–1.000 μM (Pb 2+ ) and 0.100–0.700 μM (Cd 2+ ), lower detection limits of 8.00 nM (Pb 2+ ) and 12.0 nM (Cd 2+ ) under optimal experiment condition. At last, this sensor was successfully applied to simultaneously detect Pb 2+ and Cd 2+ in paddy water and lake water with recovery rates of 97.88 ∼ 104.06% and relative standard deviation (RSD) lower than 6.24%. Most importantly, there is no significant difference between the developed electrochemical method and certified method (P < 0.05). This work provides a new idea for the simultaneous detection of heavy metal ions in the water environment. Graphical Abstract: ga1 Highlights: The support of ZIF-8-NH2 realized the three-dimensional arrangement of CNTs. The introduction of CNTs improved the poor conductivity of ZIF-8-NH2 . Bismuth film prepared in situ further enhances the response signal. The synergies of Bi, ZIF-8-NH2, and CNTs increase the detection performance.